2018
DOI: 10.3390/en11030487
|View full text |Cite
|
Sign up to set email alerts
|

Review of Research Progress on the Electrical Properties and Modification of Mineral Insulating Oils Used in Power Transformers

Abstract: Abstract:In November 2017, the first ±1100 kV high-voltage direct-current power transformer in the world, which was made by Siemens in Nurnberg, passed its type test. Meanwhile, in early 2017, a ±1000 kV ultra-high voltage (UHV) substation was officially put into operation in Tianjin, China. These examples illustrate that the era of UHV power transmission is coming. With the rapid increase in power transmission voltage, the performance requirements for the insulation of power transformers are getting higher an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(41 citation statements)
references
References 73 publications
2
35
0
2
Order By: Relevance
“…The TAN of oil with formic and levulinic acids remained lower for 1500 and 2000 h aging, while the TAN of oil with mixed acid suddenly increased up close to 2000 h of aging. The increase in the TAN of oil with mixed acids during aging can certainly be traced to the generation of high molecular weight acids resulting from oil and paper degradation [6,8,16,18]. These findings are confirmed by partitioning studies reported by Lungaard et al [8,18].…”
Section: Degree Of Polymerisation (Dpv) Before Thermal Agingsupporting
confidence: 63%
See 1 more Smart Citation
“…The TAN of oil with formic and levulinic acids remained lower for 1500 and 2000 h aging, while the TAN of oil with mixed acid suddenly increased up close to 2000 h of aging. The increase in the TAN of oil with mixed acids during aging can certainly be traced to the generation of high molecular weight acids resulting from oil and paper degradation [6,8,16,18]. These findings are confirmed by partitioning studies reported by Lungaard et al [8,18].…”
Section: Degree Of Polymerisation (Dpv) Before Thermal Agingsupporting
confidence: 63%
“…Increasing requirements for appropriate tools allowing diagnosing of power transformers non-destructively and reliably has promoted the development of modern complementary diagnostic techniques [1,2]. Research activities are still in progress worldwide to improve these techniques [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Dielectric properties, mechanical properties, and thermal behavior are the crucial properties of insulating paper. [ 29–31 ] According to literature, cellulosic paper treated with BTCA crosslinking presented enhanced mechanical properties. [ 32,33 ] BTCA crosslinking could consume hydroxyl groups and change the molecular structure and composition of cellulose, thereby reducing its polarizability.…”
Section: Introductionmentioning
confidence: 99%
“…For these purposes, maintenance policies and procedures are planned and applied to ensure the least interruption of such equipment [1][2][3]. In fact, any failure in this equipment can affect the whole network, compromise other elements in the grid and generate significant economic impacts [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its complexity and importance, the problems of aging degree of paper insulation has been object of study in many recent works [2][3][4]. Several other tests of insulation items have been an important part of transformers fault diagnosis systems, with emphasis on chromatographic oil-dissolved gas analysis, namely dissolved gas analysis (DGA) [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%